Illumination semiangle of 10−9 rad achieved in a 1.2-MV atomic resolution holography transmission electron microscope. (3rd July 2018) - Akashi, Tetsuya; Takahashi, Yoshio; Harada, Ken; Onai, Toshio; Ono, Yoshimasa A; Shinada, Hiroyuki; Murakami, Yasukazu
Abstract : The illumination semiangles of a 1.2-MV transmission electron microscope were evaluated from coherence lengths. These lengths were determined from the diameters of circular holes fully filled with Fresnel fringes. The smallest illumination semiangle of 4.0 × 10−9 rad was obtained for a circular hole with a diameter of 191 μm. Abstract: The coherency of a 1.2-MV transmission electron microscope was evaluated through illumination semiangles calculated from lengths over which Fresnel fringes can be observed. These lengths were determined from the diameters of circular holes fully filled with Fresnel fringes, i.e. this method allows lengths to be accurately measured even if micrographs are subjected to distortions. The smallest illumination semiangle of 4.0 × 10 −9 rad was obtained for a circular hole with a diameter of 191 μm. In addition, electron beam brightness was estimated to be approximately 3 × 10 14 A/m 2 ·sr from the obtained illumination semiangle values and current densities. The results provide us with essential information that can be referred to in future electron holography studies aimed at detecting weak electromagnetic fields in materials.